The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pola.26455
|View full text |Cite
|
Sign up to set email alerts
|

Photo and electrically switchable behavior of azobenzene containing pendant bent‐core liquid crystalline polymers

Abstract: New class of photo and electrically switchable azobenzene containing pendant bent‐core liquid crystalline monomers (AZBM 1, 2, and 3) and their polymers (AZBP 1, 2, and 3) are reported. The synthesized precursors, monomers, and polymers were characterized by FT‐IR, 1H, and 13C NMR spectroscopy. Thermal stability of polymers was examined by thermogravimetric analysis and revealed stable up to 260 °C. The mesophase transition of monomers and polymers are observed through polarized optical microscopy (POM) and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…In 2005, Keith et al reported the first bent core side-chain liquid crystalline polymers with a five phenyl ring core, connected with the ester, polysiloxane, as a back bone and terminal alkoxy chain. Moreover, this polymer exhibits fast ferroelectric switching and in addition, the highly interesting phenomenon of spontaneous achiral symmetry breaking, which was previously found in LC systems only for a few low molecular weight bent-core materials, was observed, (Thisayukta et al 2000;Reddy and Sadashiva 2003;Ortega et al 2003) Furthermore, Srinivasan et al (2013b) synthesized poly (meth) acrylate based BCLCPs containing six phenyl rings with different linking groups, such as: azo, azomethine and ester with higher alkyl chain (dodecyl spacer) on both terminal chains as well as the spacer. They reported that their molecules exhibited dual switching properties, Fig.…”
Section: Bent-core Side Chain Liquid Crystalline Polymers (Bclcps)mentioning
confidence: 90%
See 1 more Smart Citation
“…In 2005, Keith et al reported the first bent core side-chain liquid crystalline polymers with a five phenyl ring core, connected with the ester, polysiloxane, as a back bone and terminal alkoxy chain. Moreover, this polymer exhibits fast ferroelectric switching and in addition, the highly interesting phenomenon of spontaneous achiral symmetry breaking, which was previously found in LC systems only for a few low molecular weight bent-core materials, was observed, (Thisayukta et al 2000;Reddy and Sadashiva 2003;Ortega et al 2003) Furthermore, Srinivasan et al (2013b) synthesized poly (meth) acrylate based BCLCPs containing six phenyl rings with different linking groups, such as: azo, azomethine and ester with higher alkyl chain (dodecyl spacer) on both terminal chains as well as the spacer. They reported that their molecules exhibited dual switching properties, Fig.…”
Section: Bent-core Side Chain Liquid Crystalline Polymers (Bclcps)mentioning
confidence: 90%
“…The side-chain bent-core polymers are derived from 1,3-phenylene unit with five aromatic rings, which can be symmetric (Wang et al 2010) as well as asymmetric (Kishore et al 2009), wherein the polymerizable functional groups are generally used, are 1,3-diene (Sentman and Gin 2003), methacrylates or acrylates group (Chen et al 2007a, b) and siloxane group (Keith et al 2005). Interestingly, side-chain bent-core liquid crystalline polymers predominantly demonstrate rich mesomorphism when compared with the main-chain (Saravanan et al 2008), side-chain (Saravanan and Kannan 2010) and dendronized liquid crystalline polymers Percec 2007, 2008;Rosen et al 2009;) are classified as follows: (i) side-chain bent-core liquid crystalline polymer (SBCLCPs), (Chen et al 2007a, b;Srinivasan et al 2013b) (ii) bentcore mesogen-jacketed liquid crystalline polymers (BMJLCPs) ), (iii) central linked bent-core liquid crystalline polymer (CBCLCPs) (Srinivasan and Kannan 2011) and (iv) hydrogen-bonded side chain bent-cores liquid crystalline polymers (HBCLCPs) (Wang et al 2010), were reported based on the polymeric back bone attached to the position of bent-core mesogen pendant. Although BCLCs have been extensively investigated, bent-core side-chain polymers have so far, recorded very limited success with respect to their polar switching properties (Sentman and Gin 2003;Chen et al 2007a, b).…”
Section: Bent-core Side Chain Liquid Crystalline Polymers (Bclcps)mentioning
confidence: 97%
“…The wing with the ester linking group between the phenyl rings (14)(15)(16)(17)(18)(19) were prepared by an acylation of alkyl 3substituted-4-hydroxybenzoates (3-7) with 3-substituted-4benzyloxybenzoyl chloride (1, 2) and a subsequent deprotection of the intermediate esters 8-13 according to a literature procedure 24 (Scheme 1). In the synthesis of 4-alkoxyphenylazobenzoic acids (Scheme 2), ethyl 4-aminobenzoate (20) was firstly diazotizated and the resulting diazonium salt (21) was coupled with phenol yielding ethyl 4-(4-hydroxyphenylazo)benzoate (22). The obtained compound 22 was alkylated with 1-bromoundecane or 11-bromo-1undecene in the presence of potassium carbonate to give ester compounds (23,24), which were further hydrolyzed under basic conditions to yield corresponding acids (25,26).…”
Section: Synthesismentioning
confidence: 99%
“…In recent years, significant attention has been devoted to azo-containing symmetric and asymmetric BCLCs [3][4][5][6][7][8][9][10][11][12][13][14][15][16] , dimers combining rod-like and bent-core units 17,18 , molecules with short core units containing four aromatic rings 19,20 , and their side-chain polymers 21,22 . Additionally, photoisomerizable chromophores that allow a change in the molecular conformation by a photoreaction may open up possibilities for polar responses modulated by light.…”
Section: Introductionmentioning
confidence: 99%
“…Azo polymers have attracted considerable attention owing to their potential technological applications, such as optical storage [1], holographic image storage [2], optical switches [3][4][5] and optical diffraction devices [6] among many others. Optical switches are the devices that route an optical signal from one or more input ports to one or more output ports [7].…”
Section: Introductionmentioning
confidence: 99%